Electron spectroscopy with a diamond detector. (February 2022) - Bodie, C.S.; Lioliou, G.; Lefeuvre, G.; Barnett, A.M.
Abstract: An electronic grade single crystal chemical vapour deposition diamond was investigated as a prototype high temperature spectroscopic electron (β - particle) detector for future space science instruments. The diamond detector was coupled to a custom-built charge-sensitive preamplifier of low noise. A 63 Ni radioisotope source (endpoint energy 66 keV) was used to provide a spectrum of β - particles incident on the detector. The operating temperature of the detector/preamplifier assembly was controlled to allow its performance to be investigated between +100 °C and −20 °C, in 20 °C steps. Monte Carlo modelling was used to: a) calculate the β - particle spectrum incident on the detector; b) calculate the fraction of β - particle energy deposited into the detector; and c) predict the β - particle spectrum accumulated by the instrument. Comparison between the model and experimental data suggested that there was a 4.5 μm thick recombination region at the front of the detector. The spectrometer was demonstrated to be fully operable at temperatures, T, −20 °C ≤ T ≤ 80 °C; the results suggested that some form of polarisation phenomenon occurred in the detector at > 80 °C. This article presents the first report of an energy calibrated (≲ 50 keV) spectroscopic β - particle diamond detector. Highlights: A proof-of-principle high temperature tolerant electron spectrometer is reported. The spectrometer utilised a prototype chemical vapour deposition diamond detector. Electrons from a 63 Ni radioisotope β − particle source detected spectroscopically. The instrument operated successfully at temperatures ≤80 °C.